Eksistensi Paralegal dalam Pemberian Bantuan Hukum di Desa Tuwed, Kecamatan Melaya, Kabupaten Jembrana - Ida Ayu Tara Masari Budiana; I Made Minggu Widyantara; Luh Putu Suryani (Jurnal Konstruksi Hukum, 2022)
Indonesia, as a country based on law, In order to ensure fair legal certainty for all people, Indonesia has shown excellent development with the establishment of Law Number 16 of 2011 concerning Legal Aid. Legal aid in question is legal aid that can guarantee protection for the community, especially the poor and marginalized. As the embodiment of Law No. 16 of 2011, Paralegals are authorized to provide legal assistance in the non-litigation realm. This study aimed to determine the basic regulation regarding the role of paralegals and the existence of paralegals in the implementation of legal aid providers in Tuwed Village, Melaya District, Jembrana Regency. The results of this study are that it can be seen that the dominant community in Tuwed Village still does not understand the law, the lack of education on the law can affect the point of view, and also the behavior pattern of the community, this lack of public education can be one of the causes of a conflict. The provision of legal assistance in the non-litigation realm to increase the culture of legal awareness in the Tuwed Village community can be made by holding Legal Counseling.